Characteristics of Skin Disease related to COVID-19 infection in RSUP Dr. M. Djamil Padang: Retrospective Study - Harahap, Marina (Journal of Pakistan Association of Dermatologists, 2023)
In addition to respiratory symptoms, COVID-19 also shows cutaneous symptoms. Because the clinical features of the COVID-19 virus and other skin disorders are so similar, it can be difficult to tell one from another. However, there are still few supporting investigations. Therefore, additional research is required to make a diagnosis based on the clinical symptoms presented by several COVID-19 cases. Furthermore, another skin condition may coexist with COVID-19 infection. Aims: To identify the clinical characteristics of skin disease encountered in COVID-19-infected patients receiving therapy at Dr.M.Djamil Hospital Padang. Method: This research is a retrospective study with a sample of 49 COVID-19 patients with skin disorders treated at Dr.M.Djamil Hospital Padang from March 2020 – October 2021. Results: From the medical record data, 49 patients with skin disorders were obtained, with 25 women (51%) and 24 men (49%). With the most age being 45-65 years, as many as 19 people (39%), and the minor age being 0-11 months, as many as one person (2%). The most extended length of stay was 11-15 days for as many as 17 people (35%). Erythema, chilblains, and urticaria are some skin disorders suspected of being a skin manifestation of COVID-19 infection, e. The most common skin disorders accompanied by COVID-19 infection are SLE, irritant contact dermatitis, and ulcers. Conclusion: It can be challenging to distinguish between various skin conditions and COVID-19 skin symptoms. According to this study, the most common symptoms of COVID-19 patients were erythema, chilblains, and urticaria. Keywords : skin disease, COVID-19, Dr.M.Djamil Hospital Padang